EFFECTIVE COMMUNICATION SYSTEM AND AVIATION SAFETY: A NARRATIVE STUDY OF COMMUNITY SERVICE CONDUCTED AT SMK MUHAMMADIYAH 9 LAMONGAN - fatmawati, fatmawati; Rochmawati, Laila; Ratna Sari, Dewi; Silk Moonlight, Lady; Hariyanto, Didi (Journal of Public Transportation Community, 2025)
This study used a narrative inquiry design to reveal the outstanding participants of a community service conducted to train aviation communication and safety at SMK Muhammadiyah 9 Lamongan. This study was intended to portray the impactful benefits and contributions in determining future implications for participants’ professional development. There were seven participants chosen using a purposive sampling technique by considering inclusion criteria such as being the most active participants in the program. Data were collected using interviews and the obtained qualitative data were analyzed using a thematic approach. Results showed that there were three key points of experiences perceived by the participants, namely the importance of effective aviation communication, awareness of aviation safety, and collaboration between school staffs and students. The benefits covered increasing understanding of the aviation industry, developing practical skills, increasing awareness of safety, and forming aviation people. The future implications involved implications on education and the world of aviation, and implications in the world of transportation in Indonesia. This study suggests that the community service program conducted brings more benefits for teachers, students, the headmaster, school staff, and the facilitator. Keywords: aviation communication, aviation safety, community service, narrative inquiry